The influence of electrocoagulation to the reduction of COD, BOD, and TSS of Batik Industry wastewater - Faida Zuhria; Sarto Sarto; Imam Prasetyo (Center for Science and Technology, IAIN Surakarta, 2018)
Despite the positive economic impact of the growing Batik industry in Yogyakarta, wastewater pollution from the dyeing process poses a significant environmental threat. Initial measurements of COD, BOD, and TSS in wastewater from the dyeing process using Naphtolat and Diazo Salts exceeded the regulatory thresholds. Therefore, this study applied electrocoagulation to treat Batik wastewater. The results showed that the electrode spacing and applied voltage significantly affected the reduction of COD, BOD, and TSS in the electrocoagulation process for dye wastewater at the Batik industry